Elaboración de manual de funciones para optimizar la gestión del Benemérito Cuerpo de Bomberos del cantón Tosagua - Mero Mendieta, Wellington Orlando (2025)
This curricular integration project aimed to develop a manual of functions to optimize the management of the Benemérito Cuerpo de Bomberos (Honorary Fire Department) of the Tosagua canton. The study was carried out in three phases. First, an interview was conducted with the administrative and operational head, along with open interviews with employees. These interviews revealed the lack of a formalized manual of functions, which causes confusion in the assignment of responsibilities and affects operational efficiency. The absence of this document has led to task duplication and deficiencies in coordination, especially in critical moments. In response, a manual of functions was structured to improve the internal organization and operational efficiency of the institution. For its development, an observation sheet was used to document working conditions, and Microsoft Visio was used to create the visual organizational chart representing the staff's functions. The research was of a documentary and descriptive nature. Finally, the proposed manual was implemented, and a pilot plan was carried out to evaluate its effectiveness in optimizing management. In conclusion, the study highlights the importance of having structured management tools, such as the Manual of Functions, which not only provide clarity in responsibilities but also improve coordination among team members and strengthen the operational capacity of the Fire Department, significantly contributing to the well-being and safety of the community.